Gene Co-expression Network and Regression Analysis Identify the Transcriptomic, Physiological, and Biochemical Indicators of the Response of Alpine Woody Plant Rhododendron rex to Drought Stress - Zhou, Xiong-Li; Ma, Jin-Yan; Liu, Zhen-Dian; Dai, Ni-fei; Yang, Hui-Qin; Yang, Liu; Wang, Yue-Hua; Shen, Shi-Kang (Frontiers in Plant Science, 2022)
Increasing severity of drought stress due to global change and extreme weather has been affecting the biodiversity, function, and stability of forest ecosystems. However, despite being an important component in the alpine and subalpine vegetation in forest ecosystems, Rhododendron species have been paid rare attention in the study of molecular mechanism of tolerance or response to drought. Herein, we investigated the correlation of transcriptomic changes with the physiological and biochemical indicators of Rhododendron rex under drought stress by using the co-expression network approach and regression analysis. Compared with the control treatment, the number of significantly differentially expressed unigenes (DEGs) increased with the degree of drought stress. The DEGs were mainly enriched in the cell wall metabolic process, signaling pathways, sugar metabolism, and nitrogen metabolism. Coupled analysis of the transcriptome, physiological, and biochemical parameters indicated that the metabolic pathways were highly correlated with the physiological and biochemical indicators under drought stress, especially the chlorophyll fluorescence parameters, such as the actual photosynthetic efficiency of photosystem Ⅱ, electron transport rate, photochemical quenching coefficient, and the maximum quantum efficiency of photosystem Ⅱ photochemistry. The majority of the response genes related to the metabolic pathways, including photosynthesis, sugar metabolism, and phytohormone signal pathway, were highly expressed under drought stress. In addition, genes associated with cell wall, pectin, and galacturonan metabolism also played crucial roles in the response of R. rex to drought stress. The results provided novel insight into the molecular response of the alpine woody species under drought stress and may improve the understanding of the response of forest ecosystems to the global climate change.